The Role of Social Media in Forming Social Character at Panaragan Jaya Indah Village - Mukti, Eviana; Q, Ikhwan Aziz; Wijaya, Adi (International Journal on Advanced Science, Education, and Religion, 2025)
Modern human life is currently lived in and with social media. Social media with the power of its internet network influences social character and life, including teenagers. Social media is an internet-based platform that allows users to create, share and exchange information, ideas and content in various forms (text, images, videos, etc.) in real-time compared to conventional media such as radio, television, magazines and newspapers. Social media plays an important role in facilitating self-expression and social interaction, but it also has the potential for negative and positive influences and a lack of social character attitudes such as tolerance, respect, togetherness, mutual cooperation and empathy. This article aims to analyze the role of social media in forming social character in teenagers in Panaragan Jaya Indah village. The method used is a qualitative research method. The research sample was 6 teenagers and 2 parents. In this study, the researcher used several data collection tools, namely through observation, interviews and documentation. This researcher used a sampling technique in the form of snowball sampling to ensure data authenticity. The research results show that the role of social media in forming social character in teenagers in Panaragan Jaya Indah village is that researchers see the ethics of social media users as being keepers for filtering information, with the ethics of social media users it can be directed towards self-development, responsibility and meaning in life together. The development of social character in teenagers can be seen from how teenagers use social media according to their needs, especially the need to learn, build friendships and build positive networks with other people.